Left sided acute appendicitis with situs inversus in an elderly - an unusual case - Ahmed, Jashim Uddin; Hossain, GM Zakir; Karim, Md Masud; Hossain, ASM Iftekhar; Ahmed, Mina; Bhuya, Md Shahed Anwar (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i1.3818 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):29-31